Pneumocephalus after the Treatment of an Inoperable Superior Sulcus Tumor with Chemoradiation - Ashley Albert; Robert Allbright; Todd Nichols; Edward Farley; Srinivasan Vijayakumar (Case Reports in Oncological Medicine)
Background. Pneumocephalus is a rare phenomenon that can occur as a complication after operations involving the thoracic discs, following thoracotomy for tumor resection, and after an intracranial operation or cranial trauma. This complication frequently occurs when a tumor is located in the costovertebral angle and an operative intervention creates a tear in the dura resulting in a pleural-dural fistula. Case Presentation. We describe the case of a 58-year-old man with an inoperable superior sulcus tumor who developed pneumocephalus after the initiation of chemoradiation secondary to a pleural-dural fistula. Conclusions. Although a rare occurrence, pneumocephalus should be considered when patients with tumors in the superior sulcus treated with radiation develop neurologic symptoms characteristic of increased intracranial pressure.